Coloring Therapy on Pictures can Reduce Hospitalization Stress in Pre-School Age Children - Karnita, Ayunda Eka; Aula, Ananda; Nazirah, Arni; Aulianita, Ike; Evicha, Hesti (Health Gate, 2023)
Hospitalization of preschool children is a problematic condition experienced by children because it causes anxiety which can result in child care while in the hospital. The media is needed to divert feelings of anxiety experienced by preschool children to reduce anxiety during hospitalization. The design of this study is the Pretest Posttest Control Group Design. The sampling consisted of 32 preschool children divided into 16 control and 16 treatment groups. This study aimed to determine the effect of coloring play therapy on anxiety in preschool- aged children hospitalized at Mardi Waluyo Hospital, Blitar City. The results showed that in the control and treatment groups, p <0.05 was obtained.